1994
DOI: 10.1093/ije/23.6.1273
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Excellent Health: Different from the Determinants of III-Health?

Abstract: The processes by which excellent health is generated probably have much in common with those which generate ill-health. At the same time it is obvious that our understanding of the determinants of ill-health is better than that of the determinants of excellent health, and further study of the latter is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
4
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 0 publications
2
72
4
5
Order By: Relevance
“…This concurs with studies that found that it is better to use the continuous nature of self-evaluated health status than the dichotomized variable [31][32][33] as in the dichotomization process some of the original information will be lost. The current research showed that 16% of the original information is lost owing to the dichotomization process.…”
supporting
confidence: 88%
“…This concurs with studies that found that it is better to use the continuous nature of self-evaluated health status than the dichotomized variable [31][32][33] as in the dichotomization process some of the original information will be lost. The current research showed that 16% of the original information is lost owing to the dichotomization process.…”
supporting
confidence: 88%
“…It is now a consistent finding that educational status is a strong predictor of self-rated health (Mackenbach et al, 1994;Heistaro et al, 1996;Kawachi et al, 1999;Bobak et al, 2000). Educational status is age related in Ireland, presumably because free second level education became universally available after 1968 and has been identified by social commentators as one of the key factors in the country's more recent economic success.…”
Section: Article In Pressmentioning
confidence: 98%
“…Self-rated health is a useful proxy measure for morbidity and mortality patterns in epidemiological studies (Subramanian, Kawachi, & Kennedy, 2001;Kawachi, Kennedy, & Glass, 1999;Mackenbach, Vandenbos, Joung, Vandemheen, & Stronks, 1994;Idler & Beyamini, 1997;Heistaro, Vartiainen, & Puska, 1996;Power, Matthews, & Manor, 1998;Blakeley, Kennedy, & Kawachi, 2001). The inter-relationship between selfrated health and indicators of deprivation may differ according to gender and socio-economic status, both within and between countries (Bartley, Sacker, Firth, & Fitzpatrick, 1999;Matthews, Manor, & Power, 1999;Hraba, Lorenz, Lee, & Pechacova, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de seu caráter subjetivo, a auto-avaliação do estado de saúde é freqüentemente utilizada em inquéritos populacionais e tem especial relevância na explicação do uso de serviços de saúde. A proporção de pessoas que define seu estado de saúde como regular ou ruim é um poderoso preditor do uso de serviços de saúde e já foi associado com a mortalidade em estudos longitudinais (Mackenbach et al, 1994).…”
Section: Introductionunclassified